The Criminalization of Poaching in Hungary - Elek, Balazs (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The Criminalization of Poaching in Hungary Abstract After 2000, Hungary experienced some extraordinarily unfavorable changes with respect to poaching – in the poachers’ style, characteristics, methods and equipment. For a long time the legislation did not recognized the danger of illegal hunting. Criminological studies led to the codification of poaching law in the Criminal Code in 2012. Previously, it had only been possible to adjudicate and sanction activities related to illegal hunting through different legal frameworks, such as theft or illegal use of weapons. We must also bear in mind that the threat posed by climate change has heightened the importance of laws protecting nature and the environment; consequently, public opinion toward wildlife management and poaching must change.